2020
DOI: 10.1080/22221751.2020.1830715
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of replication-competent vesicular stomatitis virus-based recombinant viruses suitable for SARS-CoV-2 entry and neutralization assays

Abstract: Replication-competent vesicular stomatitis virus (VSV)-based recombinant viruses are useful tools for studying emerging and highly pathogenic enveloped viruses in level 2 biosafety facilities. Here, we used a replication-competent recombinant VSVs (rVSVs) encoding the spike (S) protein of SARS-CoV-2 in place of the original G glycoprotein (rVSV-eGFP-SARS-CoV-2) to develop a high-throughput entry assay for SARS-CoV-2. The S protein was incorporated into the recovered rVSV-eGFP-SARS-CoV-2 particles, which could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Several groups have now generated replication-competent VSV expressing SARS-CoV-2 spike in place of VSV-G (rcVSV-CoV2-S)( Dieterle et al, 2020 ; Li et al, 2020 )( Case, Rothlauf, Chen, Liu, et al, 2020 )( Baum et al, 2020 ; Weisblum et al, 2020 )( Yahalom-Ronen et al, 2020 )( Baum et al, 2020 ). These rcVSV-CoV2-S can be used in BSL-2 compatible virus neutralization assays (VNAs), which correlate very well with VNAs using live SARS-CoV-2 (Spearman’s r > 0.9 across multiple studies).…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have now generated replication-competent VSV expressing SARS-CoV-2 spike in place of VSV-G (rcVSV-CoV2-S)( Dieterle et al, 2020 ; Li et al, 2020 )( Case, Rothlauf, Chen, Liu, et al, 2020 )( Baum et al, 2020 ; Weisblum et al, 2020 )( Yahalom-Ronen et al, 2020 )( Baum et al, 2020 ). These rcVSV-CoV2-S can be used in BSL-2 compatible virus neutralization assays (VNAs), which correlate very well with VNAs using live SARS-CoV-2 (Spearman’s r > 0.9 across multiple studies).…”
Section: Resultsmentioning
confidence: 99%
“…Along with the aforementioned study in Letko et al, Hoffmann and colleagues used pseudotyped SARS-CoV-2 particles to show that SARS-CoV-2 infection depends on the host cell factors ACE2 and transmembrane protease, serine 2 (TMPRSS2) [36]. Li et al recovered rVSV-eGFP-SARS-CoV-2 particles and confirmed that the pseudovirus displayed entry characteristics similar to that of the WT virus, such as cell tropism and pH-dependence [48]. Ou et al used a lentiviral pseudotype system to determine cell type susceptibility, virus receptor, and entry pathway for SARS-CoV-2 [23].…”
Section: Mechanistic Study Of Viral Infection and Entrymentioning
confidence: 95%
“…Influenza A (H1N1 2009/A) was supplied by our laboratory, which was cultured in chick embryo at 35 °C for 2 days, then quantified by plaque assay, and frozen at -70 °C until use [ 36 ]. Inactivated SARS-CoV-2 virions (∼10 8 pfu/mL) were provided by courtesy of Prof. Chengfeng Qin’s laboratory in the Beijing Institute of Microbiology and Epidemiology (Beijing, China) [ [37] , [38] , [39] ]. Human throat swab specimens were obtained from healthy volunteers from Beijing Institute of Radiation Medicine (Beijing, China), with the approval of Ethics Committee of the Institute.…”
Section: Methodsmentioning
confidence: 99%